2017
DOI: 10.15376/biores.12.4.7016-7031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wood species, adhesive type, and annual ring directions on the stiffness of rail to leg mortise and tenon furniture joints

Abstract: The effects of selected factors, wood species (Fagus sylvatica L. and Picea abies L.), type of joint (haunched mortise and tenon, and haunched dovetail mortise and tenon), tenon thickness (one-third and half-joint thickness), type of adhesive (polyvinyl acetate and polyurethane adhesive), loading type (compressive and tensile), and direction of the annual rings were evaluated relative to the elastic stiffness. The testing samples were loaded by bending moment with tensile and compressive forces in the angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The results of investigation of the strength of the two most frequent joints in the upholstered furniture frames (mortise and tenon joints and double dowel joints), constructed with two wood species and the use of two adhesives (PVAc and PU) showed that the mortise and tenon joint in combination with PVAc, provided the best strength for all investigated wood species (Vassiliou et al 2016). In an investigation of effect of wood species and adhesive type on the stiffness of rail to leg mortise and tenon furniture joints, the type of glue was not important for spruce joints, whereas for beech, the stiffness of joints glued with PVAc was significantly higher than with PU adhesive (Záborský et al 2017). In comparison with PVAc, PU glue has appropriate strength, and, as they slightly expand during the hardening phase, can completely fill and cover the gaps between elements of joint (Hrovatin et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The results of investigation of the strength of the two most frequent joints in the upholstered furniture frames (mortise and tenon joints and double dowel joints), constructed with two wood species and the use of two adhesives (PVAc and PU) showed that the mortise and tenon joint in combination with PVAc, provided the best strength for all investigated wood species (Vassiliou et al 2016). In an investigation of effect of wood species and adhesive type on the stiffness of rail to leg mortise and tenon furniture joints, the type of glue was not important for spruce joints, whereas for beech, the stiffness of joints glued with PVAc was significantly higher than with PU adhesive (Záborský et al 2017). In comparison with PVAc, PU glue has appropriate strength, and, as they slightly expand during the hardening phase, can completely fill and cover the gaps between elements of joint (Hrovatin et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The permanent joints are usually composed of mortise-and-tenon (M-T) members with different wood species (Smardzewski 2008;Záborský et al 2017), glue line thickness and distribution (Kasal et al 2013;Ratnasingam and Ioras 2013;Džinčić and Živanić 2014), fits (Wang and Lee 2014;Elek et al 2020), and tenon geometry (Demirci et al 2020), which has been widely used since ancient times (Wu et al 2020). Hence, the M-T joints, especially those connected by rectangular or round blind-tenon, are favored by woodworkers and consumers due to the advantages of externally invisible and outstanding static and dynamic strength performance under a reasonable engagement (Zhang et al 2001;Erdil et al 2005;Likos et al 2013;Chevalier et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Erdil et al [16] reported that the effect of tenon width on bending moment resistance was more significant than tenon length. Furthermore, the effects of tenon thickness on the bending elastic stiffness of samples were investigated, and the results suggested that the effect of tenon thickness on the bending elastic stiffness was more significant [17].…”
Section: Introductionmentioning
confidence: 99%